Dalla “Jamesian idea” alla “Jewish idea”: il caso di "Trust" di Cynthia Ozick - Porro, Simona (Filosofia, 2019)
The present paper focuses on Trust, Cynthia Ozick’s first novel. In my reading, the text epitomizes a significant transition, in the novelist’s career, from the “Jamesian idea” to the “Jewish idea”. The “Jamesian idea” can be traced back to what Ozick calls her “youthful intoxication” with James’s work, i.e. an idolatrous worship of his prose, which led her to an unnatural isolation from life in pursuit of a literary achievement that would emulate the Master’s legendary prowess. Ozick saw her mistake when, having decided to educate herself on Jewish theology and philosophy, she became familiar with Leo Baeck’s work. His essay Romantic Religion started her on a path that she would go on to pursue throughout her long career: the exploration of Jewish theology in literary form. Written during the aforementioned self-study period, Trust is characterized by two dimensions: a conspicuous intertextual dialogue with James’s prose, and an equally noticeable emphasis on Jewish themes. In that respect, the novel shows Ozick’s evolution from an “American” writer to a “Jewish writer”.